1995
DOI: 10.2307/2946695
|View full text |Cite
|
Sign up to set email alerts
|

The Tyranny of Numbers: Confronting the Statistical Realities of the East Asian Growth Experience

Abstract: This paper documents the fimdamental role played by factor accumulation in explaining the extraoixlinary postwar growth of Hong Kong, Singapore, South Korea and Taiwan.Participation rates, educational levels and (with the exception of Hong Kong) investment rates have risen rapidly in all four economies. In addition, there have been large intersectoral reallocations of labour, with (again, excepting Hong Kong) non-agricultural and manufacturing employment growing one and a half to two times as fast as the aggre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

50
721
5
42

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,675 publications
(818 citation statements)
references
References 6 publications
50
721
5
42
Order By: Relevance
“…The flavour of this paper goes somewhat in this direction: because non-traded activities are not valued at the price that they would receive in a rich country, capital inflows are low, and aggregate productivity is lower than it would then be. One implication of our analysis is that it highlights the merit of the "transpiration" model that has been pursued by Singapore (Young, 1995, andKrugman,1994). By raising human and physical capital accumulation, countries can go a longer way than is usually expected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The flavour of this paper goes somewhat in this direction: because non-traded activities are not valued at the price that they would receive in a rich country, capital inflows are low, and aggregate productivity is lower than it would then be. One implication of our analysis is that it highlights the merit of the "transpiration" model that has been pursued by Singapore (Young, 1995, andKrugman,1994). By raising human and physical capital accumulation, countries can go a longer way than is usually expected.…”
Section: Discussionmentioning
confidence: 99%
“…Krugman (1994) referred to the "transpiration" strategy of Singapore echoing Edison's famous remark that it takes more transpiration than inspiration to innovate. Singapore's strategy is indeed one in which most of the growth has appeared to be driven by factor accumulation (in human and physical capital) rather than by total factor productivity (see Young, 1995). It also explains why migrant workers do well abroad; their human capital allows them to double their income as they move from middle-and low-income countries (excluding sub-Saharan Africa) to rich countries, and to multiply it by five if they come from sub-Saharan Africa.…”
Section: Sourcementioning
confidence: 99%
“…This link is so well established that the observation of low productivity growth among the so-called East Asian "tiger" economies during their expansion period until the '90s (e.g. Young 1992& 1995, or Kim & Lau 1994) provided the rationale for Krugman's (1994) prediction that their expansion would come to an abrupt halt -as it did indeed in the 1997-98 financial crisis. When the crisis hit, its root cause was found in the "crony capitalism" that politically wellconnected elites practiced in those countries to maximize their rent extraction.…”
Section: Considerations On Aggregate Productivity Impactmentioning
confidence: 94%
“…Looking at Hong Kong, Singapore, South Korea, and Taiwan, Young (1995) argued that East Asia was not very different from Latin America in its TFP changes. However, Singh and Trieu (1999) showed that this conclusion might be flawed, since it was based on comparing results from different methodologies.…”
Section: Sources Of Growth In East Asia: Previous Studiesmentioning
confidence: 99%
“…For example, the World Bank (1993) and Hughes (1995) examined the contribution of public policy in economic development; Kim and Lau (1994), Young (1992Young ( , 1995 and Krugman (1994) emphasized capital accumulation in the high performing East Asian economies; Sonobe and Otsuka (2001) advanced a hypothesis that capital deepening associated with transformation of industrial structure has been the major factor for sustaining growth for a long period in East Asia; Hayami and Ogasawara (1999) argued that Japan has continued to depend more heavily on physical capital accumulation mainly due to its characteristic of borrowed-technology based economic growth; and Trieu (1997, 1999) focused more on the role of technological change. Despite many differences in data and analytical methodologies, these and numerous other studies tended to have one common assumption in analyzing the relative role of input accumulation and productivity change: they assumed that production was always on the frontier without any slack in production.…”
Section: Introductionmentioning
confidence: 99%